The science-practice gap and employee engagement: It's a matter of principle - Meyer, John (2013)
The science of Industrial/Organisational Psychology has generated a large body of knowledge over the last century, yet we continue to lament the fact that what we have learned is not being applied to the extent that it should. Practitioners argue that the science is not accessible, fails to address important current issues, and proceeds at such a pace that it is often outdated before it becomes available. To the contrary, I argue that the value of science is the discovery of valid and generalizable principles that can be applied to work-relevant issues as they become current. The challenge is to identify these principles and to translate them into a set of heuristic guidelines that can be used to facilitate managerial decision making. I illustrate this process as it might be applied in the case of employee engagement, but argue that it can be applied to other "hot issues," both current and future.